Best practices in L2 English source use pedagogy: A thematic review and synthesis of empirical studies. (November 2016) - Liu, Gi-Zen; Lin, Vivien; Kou, Xiaojing; Wang, Hong-You
Abstract: There is an urgency to improve source use among non-native speakers of English in the globalized era. This review examines problems and causes of second language (L2) English source misuse in the English as a Second Language (ESL) and English as a Foreign Language (EFL) environments, and proposes remedies for the problems. Thematic analysis resulted in issues related to L2 English misuse under the categories of (a) source use norms, (b) source use acquisition, and (c) ethical practice in L2 academic writing from 53 empirical studies. Furthermore, nine recommendations for L2 English source use pedagogy were derived to (a) ensure transparency in definitions, guidelines, and expectations, (b) build source use knowledge, and (c) engage L2 English writers in continuous practice and autonomous development of plagiarism avoidance. Finally, the authors provide an inter-relational network among the nine themes as well as suggestions for enhancing L2 source use policies and education among institutions and practitioners aiming to improve source use for L2 English writers. Highlights: Nine themes on ESL and EFL source use emerged from 53 empirical studies. L2 English source use pedagogy should ensure transparency, knowledge, and engagement. L2 English source use themes inter-relate in cultural, language, and educational dimensions.